Consensus of linear discrete-time multi-agent systems based on full-dimensional state observer. (2016) - Xu, Yong; Gao, Jinfeng; Shi, Ting; Gu, Minming; Lei, Meizhen
This paper considers consensus of linear discrete-time multi-agent systems (MASs) based on full-dimensional state observer. Compared to Cheng et al. (2011), a new consensus protocol for the discrete-time MASs with virtual communication network topology is proposed and has faster convergence speed. Under the new consensus protocol, each agent gets not only its own state through the full-dimensional observer, but also the states of its neighbours and its instantaneous neighbours to reach consensus. Necessary and sufficient conditions of consensus for the MASs are presented. Finally, an example is provided to illustrate the effectiveness of the proposed method, and extended to directed topology case.